A role for auto-immunity in chronic rhinosinusitis? Lessons learned from sub-epidermal bullous disorders of the skin. Issue 1 (December 2016) - Lefrançois, Philippe; Chapdelaine, Hugo; Côté, Benoît; Desrosiers, Martin
Abstract Chronic rhinosinusitis (CRS) is a frequent chronic condition, which has origins in complex interactions between genetic, immunological and microbial factors. The role of auto-immunity in CRS remains unclear, although recent studies have started to emerge in CRS patient refractory to maximal medical management. We discuss the possible auto-immunity link between CRS and other skin diseases, in particular acquired bullous dermatoses, and review the current evidence. We raise additional considerations for auto-immunity from both research and clinical standpoints.